Nasolacrimal Duct Probing under Topical Anesthesia for Congenital Nasolacrimal Duct Obstruction in Taiwan - Chih-Heng Hung; Yi-Chun Chen; Shun-Ling Lin; Wei-Lun Chen (Pediatrics and Neonatology)
To report the success rates of office probing for congenital nasolacrimal duct obstruction (NLDO) among children of different age groups in Taiwan. Methods: In this single-center, retrospective study, 564 eyes of 477 patients under the age of 5 years diagnosed with congenital NLDO were treated in a stepwise manner between 2001 and 2013. For infants aged < 6 months, treatment with massage and observation was suggested, followed by deferred probing under topical anesthesia if symptoms persisted. However, in cases of severe infection, immediate probing was suggested. In children aged > 6 months, office probing was usually highly recommended. Those with probing failures received either a second probing or silicone intubation. Treatment success was defined as anatomic patency by immediate irrigation after probing and absence of epiphora or mucous discharge at the follow-up visit. Results: Primary probing was successful in 457 of 564 eyes (success rate: 81%). The success rate of primary probing was negatively correlated with increasing age: 90.1% (163/181), 79.6% (164/206), 76.8% (73/95), 73.5% (36/49), 75% (18/24), and 33% (3/9) for the age groups of 0 to <6 months, 6 to <12 months, 12 to <18 months, 18 to <24 months, 24 to <36 months, and 36–60 months, respectively (p < 0.001, Fisher's exact test). The second probing was successful in 52 of 81 eyes. In total, probing was successful in 509 of 564 eyes (success rate: 90.2%). Conclusion: Office probing is safe and effective for treating congenital NLDO. The success rate of primary probing decreases significantly with age.